A mixed methods study of individual and organizational factors that affect implementation of interventions for children with autism in public schools. (December 2016) - Locke, Jill; Beidas, Rinad; Marcus, Steven; Stahmer, Aubyn; Aarons, Gregory; Lyon, Aaron; Cannuscio, Carolyn; Barg, Frances; Dorsey, Shannon; Mandell, David
Abstract Background The significant lifelong impairments associated with autism spectrum disorder (ASD), combined with the growing number of children diagnosed with ASD, have created urgency in improving school-based quality of care. Although many interventions have shown efficacy in university-based research, few have been effectively implemented and sustained in schools, the primary setting in which children with ASD receive services. Individual- and organizational-level factors have been shown to predict the implementation of evidence-based interventions (EBIs) for the prevention and treatment of other mental disorders in schools, and may be potential targets for implementation strategies in the successful use of autism EBIs in schools. The purpose of this study is to examine the individual- and organizational-level factors associated with the implementation of EBIs for children with ASD in public schools. Methods We will apply the Domitrovich and colleagues (2008) framework that examines the influence of contextual factors (i.e., individual- and organizational-level factors) on intervention implementation in schools. We utilize mixed methods to quantitatively test whether the factors identified in the Domitrovich and colleagues (2008) framework are associated with the implementation of autism EBIs, and use qualitative methods to provide a more comprehensive understanding of the factors associated with successful implementation and sustainment of these interventions with the goal of tailoring implementation strategies. Discussion The results of this study will provide an in-depth understanding of individual- and organizational-level factors that influence the successful implementation of EBIs for children with ASD in public schools. These data will inform potential implementation targets and tailoring of strategies that will help schools overcome barriers to implementation and ultimately improve the services and outcomes for children with ASD.